Mediating Marketing Digitalization in the Relationship of Online Shopping Experience and Trust in E-commerce Platforms to Consumer Behavior: Evidence from Indonesia - Windi, Windi; Harisandi, Prasetyo; Muhsoni, Ridwan (Prodi Pendidikan Sejarah Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Sumatera, 2025)
In Indonesia's rapidly expanding e-commerce sector, this study examines the mediating function that marketing digitalization plays in the relationship between online shopping experience, trust in e-commerce platforms, and consumer behavior. A quantitative methodology was utilized, which involved surveying 300 Indonesian consumers who shop online. The findings show a strong positive correlation between the online buying experience and customer behavior, with trust in e-commerce platforms being positively correlated with both consumer behavior and marketing digitalization. Furthermore, it was discovered that marketing digitalization entirely mediates the association between online shopping experience and customer behavior and somewhat mediates the relationship between online shopping experience and trust in e-commerce platforms. These results highlight how crucial it is to offer a flawless online shopping experience, cultivate customer trust, and use digital marketing techniques to shape consumer behavior in Indonesia's ever-changing e-commerce sector.